Copper and zinc stress in aquatic fungi: the role of cellular antioxidant defences - Azevedo, Maria Manuel (2004)
Resumo da comunicação apresentada no "IX International Marine and Freshwater Mycology Symposium", Chiang Mai, Tailândia, 14 a 19 Novembro 2004.